Select Skeletal Muscle mRNAs Related to Exercise Adaptation Are Minimally Affected by Different Pre-exercise Meals that Differ in Macronutrient Profile - Knuiman, Pim; Hopman, Maria T. E.; Wouters, Jeroen A.; Mensink, Marco (Frontiers in Physiology, 2018)
Background: Substantial research has been done on the impact of carbohydrate and fat availability on endurance exercise adaptation, though its role in the acute adaptive response to resistance exercise has yet to be fully characterised. Purpose: We aimed to assess the effects of a pre-resistance exercise isocaloric mixed meal containing different amounts of carbohydrates and fat, on post-resistance exercise gene expression associated with muscle adaptation. Methods: Thirteen young (age 21.2 ± 1.6 year), recreationally trained (VO2max 51.3 ± 4.8 ml/kg/min) men undertook an aerobic exercise session of 90-min continuous cycling (70% VO2max) in the morning with pre- and post-exercise protein ingestion (10g and 15g casein in a 500ml beverage pre- and post-exercise, respectively). Subjects then rested for two hours and were provided with a meal consisting of either 3207 kJ; 52g protein; 51g fat and 23g carbohydrate (FAT) or 3124 kJ; 53g protein; 9g fat; and 109g carbohydrate (CHO). Two hours after the meal, subjects completed 5 x 8 repetitions (80% 1-RM) for both bilateral leg press and leg extension directly followed by 25g of whey protein (500 ml beverage). Muscle biopsies were obtained from the vastus lateralis at baseline (morning) and 1 h and 3 h post-resistance exercise (afternoon) to determine intramuscular mRNA response. Results: Muscle glycogen levels were significantly decreased post-resistance exercise, without any differences between conditions. Plasma free fatty acids increased significantly after the mixed meal in the FAT condition, while glucose and insulin were higher in the CHO condition. However, PDK4 mRNA quantity was significantly higher in the FAT condition at 3 h post-resistance exercise compared to CHO. HBEGF, INSIG1, MAFbx, MURF1, SIRT1 and myostatin responded solely as a result of exercise without any differences between the CHO and FAT group. FOXO3A, IGF-1, PGC-1α, and VCP expression levels remained unchanged over the course of the day. Conclusion: We conclude that mRNA quantity associated with muscle adaptation after resistance exercise is not affected by a difference in pre-exercise nutrient availability. PDK4 was differentially expressed between CHO and FAT groups, suggesting a potential shift towards fat oxidation and reduced glucose oxidation in the FAT group.